SEMANTIC STUDY ON ENGLISH TERMS USED IN SOCIAL NETWORK - Reem Reem (The Ellite of Unira, 2018)
Semantic study is one of the branches of linguistic study. Semantic is the study of the meaning that humans use the language to express. It investigates meanings of basic expressions and how is meaning assigned to complex expressions based on the meaning of simpler expressions and syntactic structure. In a social life, semantic takes part in it. Sometimes people get difficulty at the beginning of language study caused by the misunderstanding of the meaning. Especially from a particular field, Such as social network terms. Each social network site has its own term that makes people confused to recognize each of them. So, this study focuses on semantic study on English terms that used in social network. This study was designed by using descriptive qualitative method. The sources of data were taken mostly from internet that related to the social network sites, which is facebook, Myspace, Twitter and Yahoo!Messenger. in these social network sites, the researcher concluded that there are 96 English terms that have contextual meaning. 30 English terms from Facebook, 16 English terms from Myspace, 23 English terms from Twitter and 27 English Terms from Yahoo! Messenger has been studied. The researcher hopes this study will be useful for people to enrich their knowledge about semantics and the English terms used in social network. Moreover, this research may inspire other researchers to make other studies dealing with semantics and other linguistics branches.